Computational and Experimental Study of the Effect of Solidity and Aspect Ratio of a Helical Turbine for Energy Generation in a Model Gravitational Water Vortex Power Plant - Joshi, Shubhash; Jha, Ajay Kumar (Journal of Advanced College of Engineering and Management, 2021)
Gravitational Water Vortex power plant is a relatively new plant used to generate hydropower from low head rivers and canals. There has been an increase in research in the field of runner design and canal design for GWVPPs throughout the world. As no definite equations are formulated in case of runners used in a GWVPP, they are currently produced by hit and trial method. This research focuses on studying about the use of a pure reaction turbine, Gorlov turbine, to generate power from a GWVPP. ANSYS Fluent was used to perform computational study while the experimental study was done using helical turbine blades fabricated using a 3-D printer. The energy generated is very low compared to the impulse turbines. Both the computational and experimental study shows that when increasing the aspect ratio of the turbine but keeping the solidity same, the efficiency is increased significantly. However, the studies also show that on increasing the solidity, the efficiency seems to decrease. All the turbines used submerged to 3 different depts and all the results show that increasing the submergence increased the efficiency.